EFFECT OF SOLVENT BEHAVIOR OF NALIDIXIC ACID BY ULTRAVIOLET SPECTROSCOPY - Daniel A. Palacio; Bernabé L. Rivas; Carla Muñoz Vega (Journal of the Chilean Chemical Society, 2020)
One of the most widely used pharmaceuticals of the antibiotic type is quinolones. Nalidixic acid belongs to this family of antibiotics is widely used in both human and veterinary medicine. The objective of this work is to show the behavior of nalidixic acid in co-solvent mixtures, in order to study in the near future the removal of this antibiotic in aqueous solutions or mixtures of water with solvents. The study was carried out by preparing a standard solution containing 25 mg of nalidixic acid in 50 mL in different solvent mixtures. Subsequently, 20 mg L-1 solutions were prepared using the same mixture of solvents (acetone: water, methanol: water and ethanol: water) to be scanned for wavelengths by UV-Vis spectroscopy. The spectra showed signal displacement in all the mixtures when there was an increase with respect to the water contents due to the interaction of the water with the acid group of the antibiotic. While in mixtures of methanol: water and ethanol: water solutions, there is a variation of the signal intensities. As a conclusion, it can be said that it is important to consider the solubility capacity of this antibiotic in different solvents for the purposes of removal studies of this type of emerging contaminants of the antibiotic type.